Factors Influencing Intrinsic Capacity Decline and Its Measurements among Geriatrics: A Scoping Review - Nurhazrina Binti Noordin; Siriphorn, Akkradate; Yu, Chye Wah; Justine, Maria (Journal of Liaquat University of Medical & Health Sciences, 2026)
Healthy ageing is dependent on intrinsic capacity (IC), and knowledge of its associated factors is essential for achieving the goal of healthy ageing. This review examines the factors influencing IC decline in older adults by exploring the scope, characteristics, and impacts on healthcare outcomes. Three databases —CINAHL, Web of Science, and PubMed — were systematically searched for full-text English articles published between January 2020 and June 2024 to capture comprehensive evidence across the WHO-ICOPE domains, encompassing allied health, biomedical, and multidisciplinary research on intrinsic capacity in older adults. Studies on "intrinsic capacity", "older adults," and "health outcomes" were selected through a six-step review process conducted by two reviewers, with a third reviewer resolving any conflicts. This scoping review encompasses 12 studies from 2020 to 2023, spanning eight countries, with sample sizes ranging from 100 to 25,000. Data were extracted using a standardized form and synthesized through descriptive summaries and thematic analysis to map key concepts and identify evidence gaps across the six WHO-ICOPE domains. The studies examine factors related to intrinsic capacity (IC) decline, including environment, lifestyle, education, and sensory function. Five studies are cross-sectional, and seven are longitudinal. Key influences on the health of older adults include environmental, lifestyle, and sensory factors. Future studies should address the identified evidence gaps by including larger and more diverse populations, expanding research to underrepresented regions, and adopting standardized WHO-ICOPE-aligned outcome measures. Further work should also explore the feasibility, implementation, and cost-effectiveness of multi-domain interventions to inform practice and policy in geriatric care.